Leveraging farmer federation to social capital and motivation enhancement for sustainable Ipomoea reptans farming in East Java, Indonesia - SUSANTO, HERI; SYAHRIAL, RAMON; DIANTO, ANDRI KRISNA (Smujo International, 2025)
Abstract. Susanto H, Syahrial R, Dianto AK. 2025. Leveraging farmer federation to social capital and motivation enhancement for sustainable Ipomoea reptans farming in East Java, Indonesia. Asian J Agric 9: 870-880. This study examines the relationships between social capital, farmer motivation, and the mediating role of Farmer Group Federations (Gapoktan) in improving the productivity and sustainability of Ipomoea reptans farming in Balongpanggang, Indonesia. A mixed-methods design was employed using census data from 35 farmers and analyzed through Structural Equation Modeling Partial Least Squares (SEM PLS). The findings show that social capital has a positive and significant association with Gapoktan partnerships, while farmer motivation does not show a significant direct relationship. Gapoktan partnerships significantly improve agricultural productivity and the adoption of sustainable practices. Gapoktan also mediates the relationship between farmer motivation and productivity but does not mediate the relationships between motivation and sustainability or between social capital and either outcome. These results indicate that Gapoktan serves as an important institutional mechanism that converts collective farmer relationships into productive outcomes, with social capital emerging as a stronger predictor than individual motivation. Strengthening Gapoktan’s institutional capacity is therefore essential to optimize farmer networks, reinforce collective action, and promote sustainable agricultural development. The study highlights the need for institutional strengthening in rural farming systems to translate social assets into measurable gains in productivity and sustainability.